Can neck exercises enhance the activation of the semispinalis cervicis relative to the splenius capitis at specific spinal levels?. Issue 5 (October 2015) - Schomacher, Jochen; Erlenwein, Joachim; Dieterich, Angela; Petzke, Frank; Falla, Deborah
Abstract The deep cervical extensor, semispinalis cervicis, displays changes in behaviour and structure in people with chronic neck pain yet there is limited knowledge on how activation of this muscle can be emphasized during training. Using intramuscular electromyography (EMG), this study investigated the activity of the deep semispinalis cervicis and the superficial splenius capitis muscle at two spinal levels (C2 and C5) in ten healthy volunteers during a series of neck exercises: 1. Traction and compression, 2. Resistance applied in either flexion or extension at the occiput, at the level of the vertebral arch of C1 and of C4, and 3. Maintaining the neck in neutral while inclined on the elbows, with and without resistance at C4. The ratio between semispinalis cervicis and the splenius capitis EMG amplitude was quantified as an indication of whether the exercise could emphasize the activation of the semispinalis cervicis muscle relative to the splenius capitis. Manual resistance applied in extension over the vertebral arch emphasized the activation of the semispinalis cervicis relative to the splenius capitis at the spinal level directly caudal to the site of resistance (ratio: 2.0 ± 1.1 measured at C5 with resistance at C4 and 2.1 ± 1.2 measured at C2 with resistance at C1). This study confirmed the possibility of emphasizing the activation of the semispinalis cervicis relative to the splenius capitis which may be relevant for targeted exercise interventions for this deep extensor muscle. Further studies are required to investigate the clinical efficacy of these exercises for people with neck pain.